2004
DOI: 10.1213/01.ane.0000130616.57678.80
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Assessment for the Reversibility of Rocuronium-Induced Neuromuscular Blockade During Propofol or Sevoflurane Anesthesia

Abstract: We sought to determine whether tactile train-of-four (TOF) count can predict the efficacy of neostigmine administration for rocuronium-induced blockade during propofol or sevoflurane anesthesia, and to follow subsequent recovery until the TOF ratio reached 0.9. One-hundred-sixty patients, divided into eight equal groups, were randomly allocated to maintenance of anesthesia with propofol or sevoflurane. The tactile response of the adductor pollicis to TOF stimulation was evaluated on one arm, and the mechanomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 20 publications
1
50
0
3
Order By: Relevance
“…For the moderate neuromuscular block using cisatracurium, Kirkegaard et al concluded that a dose of 0.07 mg/kg neostigmine produces block reversibility (TOF = 0.9) in 20 minutes (7-71 minutes) [45]. Kim and his team established that the average time required to reverse moderate block with rocuronium, using the same dose of neostigmine, is 23 minutes (range 8-57) [46]. The recommended sugammadex dose for reversing moderate block is 2 mg/kg [16].…”
Section: When and How We Should Antagonize Nmba?mentioning
confidence: 99%
“…For the moderate neuromuscular block using cisatracurium, Kirkegaard et al concluded that a dose of 0.07 mg/kg neostigmine produces block reversibility (TOF = 0.9) in 20 minutes (7-71 minutes) [45]. Kim and his team established that the average time required to reverse moderate block with rocuronium, using the same dose of neostigmine, is 23 minutes (range 8-57) [46]. The recommended sugammadex dose for reversing moderate block is 2 mg/kg [16].…”
Section: When and How We Should Antagonize Nmba?mentioning
confidence: 99%
“…This is why it is recommended to attempt reversal only when significant recovery has already taken place, that is the presence of at least two, and preferably four, twitches in response to train-of-four (TOF) stimulation is documented. 5 The second problem related to anticholinesterase agents is the cardiovascular sideeffect profile, even with the co-administration of an anticholinergic. By binding to the neuromuscular blocking agent and not to any receptor, sugammadex has the potential to solve the drawbacks of neostigmine and other anticholinesterase agents.…”
mentioning
confidence: 99%
“…When four TOF responses are observed, even if fade is seen, neostigmine is considered reasonably effective, and one expects adequate neuromuscular recovery, now regarded as being a TOF ratio > 0.9, to occur within five to 15 min, with no recurarization. 5 The rules will change markedly with the introduction of sugammadex. The requirement to obtain some degree of spontaneous recovery will no longer be present.…”
mentioning
confidence: 99%
See 2 more Smart Citations